2019
DOI: 10.1515/dx-2019-0048
|View full text |Cite
|
Sign up to set email alerts
|

Updates to referring clinicians regarding critically ill children admitted to the pediatric intensive care unit: a state-wide survey

Abstract: BackgroundFront-line clinicians are expected to make accurate and timely diagnostic decisions before transferring patients to the pediatric intensive care unit (PICU) but may not always learn their patients’ outcomes. We evaluated the characteristics of post-transfer updates received by referring clinicians regarding PICU patients and determined preferences regarding content, delivery, and timing of such updates.MethodsWe administered an electronic cross-sectional survey to Iowa clinicians who billed for ≥5 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Consistent formal feedback of patient management and outcomes to referring physicians is an important step to effect positive change in patient care. 33 The most effective feedback occurs when it is received from people who have developed relationships with referring hospitals and clinicians, fostering a culture of collaborative learning. 33 We have found that developing a relationship with hospitals before initiation of the feedback process has allowed us to be more successful with effecting change in practice management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent formal feedback of patient management and outcomes to referring physicians is an important step to effect positive change in patient care. 33 The most effective feedback occurs when it is received from people who have developed relationships with referring hospitals and clinicians, fostering a culture of collaborative learning. 33 We have found that developing a relationship with hospitals before initiation of the feedback process has allowed us to be more successful with effecting change in practice management.…”
Section: Discussionmentioning
confidence: 99%
“…Hospitals may not be as receptive to feedback and may perceive feedback as criticism. Consistent formal feedback of patient management and outcomes to referring physicians is an important step to effect positive change in patient care 33 . The most effective feedback occurs when it is received from people who have developed relationships with referring hospitals and clinicians, fostering a culture of collaborative learning 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We conducted two focus groups of ED physicians (six UI ED physicians and six non-UI-affiliated referring physicians) to substantiate our earlier survey indicating the gap in feedback 13 and explore physicians' perceptions of the relevance of receiving consistent patient outcome information. Referring physicians noted the various unsystematic ways in which they find out what happened to their patients.…”
Section: Methodsmentioning
confidence: 99%
“…Among clinicians who obtained feedback,13% received information they did not expect; 40% of these clinicians indicated that this experience changed their practice. 13…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation